Nonlinear Lattice Within Supersymmetric Quantum Mechanics Formalism - Drigo Filho, Elso [UNESP]; Ricotta, R. M. (Iop Publishing Ltd, 2012)
In the last decades, the study of nonlinear one dimensional lattices has attracted much attention of the scientific community. One of these lattices is related to a simplified model for the DNA molecule, allowing to recover experimental results, such as the denaturation of DNA double helix. Inspired by this model we construct a Hamiltonian for a reflectionless potential through the Supersymmetric Quantum Mechanics formalism, SQM. Thermodynamical properties of such one dimensional lattice are evaluated aming possible biological applications.